Validity and reliability of a smartphone-based photographic method for detection of dental caries in adults for use in teledentistry - Lamas-Lara, Victor F.; Mattos-Vela, Manuel A.; Evaristo-Chiyong, Teresa A.; Guerrero, Maria Eugenia; Jiménez-Yano, Juan F.; Gómez-Meza, Dora N. (Frontiers in Oral Health, 2025)
IntroductionWith the arrival of the COVID-19 pandemic, the role of teledentistry increased its need for implementation. In this sense, the study aimed to validate a smartphone-based remote photographic method for diagnosing dental caries in adults attending a polyclinic in Lima, Peru.MethodsA cross-sectional, descriptive research was conducted; 87 patients were selected, and 2020 teeth were evaluated. Each participant underwent a clinical diagnosis of dental caries by two trained and calibrated dentists, considering the diagnostic criteria of the WHO; during the same visit, after the clinical examination, a family member of the patient was instructed to take a photographic record with a cell phone, through a video. Five photographs of the dental arches were recorded, where the centering of images, resolution, and visualization of all the teeth were evaluated. The photographic evaluation was performed by two independent evaluators blinded to the visual evaluation performed, following the same criteria as the clinical visual evaluation. For the data analysis, Cohen's kappa index was determined for interexaminer reliability; sensitivity, specificity, and positive and negative predictive values were obtained.ResultsOverall, high sensitivity: 90.19% [Interquartile 95% (CI): 88.23–92.16]; and specificity: 95.15% (95% CI: 93.83–96.47). The interexaminer agreement was almost perfect, with a kappa of 0.935 and 0.974 for clinical and photographic evaluation, respectively.ConclusionsIt is concluded that the photographic method using a smartphone has demonstrated a satisfactory level of caries detection in adults.